2022
DOI: 10.3390/vaccines10030382
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of SARS-CoV-2 BNT162b2 Vaccine in People with Diabetes: A Prospective Observational Study

Abstract: The mRNA-based BNT162b2 vaccine has demonstrated high efficacy against severe SARS-CoV-2. However, data regarding immune response in people with diabetes mellitus (DM) after vaccination with the BNT162b2 vaccine are limited. In this prospective observational study, we examined humoral immune response in participants with and without DM after vaccination with the BNT162b2 mRNA vaccine. A total of 174 participants (58 with and 116 without diabetes, matched for age) were included. Antibodies were measured 21 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…However, hyperglycemia in uncontrolled diabetes results in weak immunity, indicating that poor glycemic control can indeed impair the antibody producing branch of adaptive immunity. Two independent studies reported similar results (186,187).…”
Section: Response To Vaccination and Metabolically Active Therapeuticsmentioning
confidence: 60%
“…However, hyperglycemia in uncontrolled diabetes results in weak immunity, indicating that poor glycemic control can indeed impair the antibody producing branch of adaptive immunity. Two independent studies reported similar results (186,187).…”
Section: Response To Vaccination and Metabolically Active Therapeuticsmentioning
confidence: 60%
“…One study’s population consisted of DM patients, but the number was not mentioned ( 27 ). Eleven of the studies had controls ( 27 , 29 , 30 , 32 35 , 37 , 38 , 41 , 42 ), while five of them did not ( 27 , 28 , 31 , 39 , 40 ). Type of diabetes was specifically mentioned in six studies; four were T2DM ( 27 , 32 , 34 , 42 ), and two were both T1DM and T2DM ( 35 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the studies had controls ( 27 , 29 , 30 , 32 35 , 37 , 38 , 41 , 42 ), while five of them did not ( 27 , 28 , 31 , 39 , 40 ). Type of diabetes was specifically mentioned in six studies; four were T2DM ( 27 , 32 , 34 , 42 ), and two were both T1DM and T2DM ( 35 , 38 ). In terms of the type of vaccine; BNT162b2 was assessed in twelve of the studies ( 27 , 28 , 30 , 32 , 33 , 35 , 37 39 , 41 , 42 ), mRNA-1273 was assessed in two of the studies ( 32 , 35 ), CoronaVac, Sinopharm or SinoVac were assessed in four studies ( 28 , 29 , 31 , 39 ), ChAdOx1-S was assessed in four studies ( 32 , 34 , 35 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been lots of studies showing comparable safety and effectiveness of SARS-CoV-2 vaccine in special population (e.g., diabetes, solid organ transplant, autoimmune disease patients), which greatly promoted the vaccination in senior people with and without underlying diseases [18][19][20][21] . Systematic evaluation of inactivated SARS-CoV-2 vaccine safety and effectiveness in people with common diseases has been rare.…”
Section: Introductionmentioning
confidence: 99%